FINANCIAL COST ANALYSIS OF PUBLIC WATER SUPPLY PROJECTS IN JOS METROPOLIS, PLATEAU STATE, NIGERIA - ALI, ANDESIKUTEB YAKUBU; DANJUMA, YUSUF IBRAHIM; VIVAN, 3EZRA LEKWOT (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Water is precious and indispensable resources that support man, his activities and the general function of an ecosystem. The increasing demand for water resulting from economic growth, climate change, pollution and concomitant population growth, therefore work to increase pressure on water and the cost of its treatment. This Study examines the financial costs of water supply projects in Jos metropolis to the government of Plateau State. Only documented secondary sources of data from Plateau State Water Board (PSWB) were explored for information on number of subscribers and the cost incurred across the years for water production and supply. Frequency tables were used for presentation and analysis of data. The study found among other things that, the total sum of N5, 089,516,239.55 was spent on operations, maintenance and repairs in different areas of PSWB operations. The cost of expansion of water supply projects on the other hand was put at N4, 678,172,065.70, the years 2016, 2017 and 2018 recorded the highest with the peak of N7.049bn in 2018. It concluded that the cost incurred in the development of water supply projects are very exorbitant and may outweigh the expected year on year returns. Recommendations such as cost sharing between government and private sector through public private partnership to ease the burden of these expenditures on them; Plateau State Water Board should embark on serious recovery drive to recover any accumulated receivables over time ;PSWB should also automate some processes to cut down cost of production, the government should provide alternative compensational fishing grounds, settlements and farmlands to the original owners; the Board should explore alternate power sources to cut the costs on electricity supply and amount spent on diesel for their operational activities.